O humor em O cheiro do ralo, de Lourenço Mutarelli - Negreli, Pâmella Possatti (2019)
It analyzes the humor in Lourenço Mutarelli's "O Cheiro do Ralo" (2011), a Brazilian novel in which the plot, as the title predicts, revolves around the unbearable smell (of "shit") that comes from the drain, which makes the protagonist paranoid, because he cannot stop the bad smell and believes that the drain is the gate to hell. It studies the narrative literary humor from the linguistic point of view, considering the studies of Vladímir Propp and Luiz Carlos Travaglia; historiographical, from the observations of Georges Minois and Quentin Skinner, and philosophical, based on the reflections of Yves de La Taille. It analyzes Mutarelli's novel from two aspects: existential humor and sad humor. It perceives that the humorous resources most used in the novel, irony, exaggeration and the expectancy violation guide the narrative to the close connection of Mutarellian humor with the grotesque and the coprological, whose effect is the feeling of sadness.